Pelindungan Konsumen terhadap Pelaku Usaha yang Tidak Melakukan Pencatatan Berita Acara Undian dengan Akta Autentik - Eko Ramdani (CV Rewang Rencang, 2025)
This study analyzes consumer protection for business actors who do not record lottery minutes with authentic deeds. Using normative methods, this study examines the legal obligations of recording and liability of business actors. The results show that non-compliance with these obligations has the potential to result in legal sanctions and losses for consumers. Therefore, it is necessary to strengthen regulations to ensure transparency and accountability in organizing lottery prizes, in order to effectively protect consumer rights.